Математическое описание поверхности ротора гидросепаратора угольной суспензии - Никитин, Н. И.; Москаленко, В. В. (НТУ "ХПИ", 2007)
У статті розглядаються конструктивні особливості гідросепаратора вугільної суспензії. Наведено математичний опис для складання варіантів конструкції поверхні ротора апарату. Результати призначені для математичного моделювання роботи гідросепаратора із застосуванням ЕОМ.

In this article design features of the hydroseparator of coal suspension are investigated. The mathematical description of the surface of rotor device for drawing up of its various constructive variants is given. The results are intended for mathematical modeling of hydroseparator action with usage of computer.
Keywords: функции поверхности; математический конструктор; полутор; визуальный интерфейс